Current status of acceptance and commitment therapy for chronic pain: a narrative review - Feliu-Soler A; Montesinos F; Gutiérrez-Martínez O; Scott W; McCracken LM; Luciano JV (Journal of Pain Research, 2018)
Albert Feliu-Soler,1,2 Francisco Montesinos,3,4 Olga Gutiérrez-Martínez,5 Whitney Scott,6 Lance M McCracken,6,7 Juan V Luciano1,2 1Teaching, Research and Innovation Unit, Parc Sanitari Sant Joan de Déu, St. Boi de Llobregat, Spain; 2Primary Care Prevention and Health Promotion Research Network (RedIAPP), Madrid, Spain; 3Department of Psychology, Faculty of Biomedical and Health Sciences, Universidad Europea de Madrid, Madrid, Spain; 4Instituto ACT, Madrid, Spain; 5Fundación Biomédica Galicia Sur, Vigo, Spain; 6Department of Psychology, Institute of Psychiatry, Psychology and Neuroscience, King’s College London, London, UK; 7INPUT Pain Management, Guys and St Thomas NHSFT, London, UK Abstract: It is well known that chronic pain is prevalent, complex to manage, and associated with high costs, in health care and society in general. Thanks to advances in new forms of cognitive behavioral therapy (known as third-wave CBT), currently clinicians and researchers have an empirically validated psychological treatment with increasing research support for the treatment of chronic pain. This treatment is called acceptance and commitment therapy (ACT). The main aim of this paper is to provide a narrative review that summarizes and integrates the current state of knowledge of ACT in the management of chronic pain as well as discuss current challenges and opportunities for progress. Based on the psychological flexibility model, ACT extends previous forms of CBT and integrates many CBT-related variables into six core therapeutic processes. ACT is a process-based therapy that fosters openness, awareness, and engagement through a wide range of methods, including exposure-based and experiential methods, metaphors, and values clarification. To our knowledge, there are three published systematic reviews and meta-analyses that support the effectiveness of ACT for chronic pain and many studies focused on specific processes derived from the psychological flexibility model. There is also promising support for the cost-effectiveness of ACT; however, the current evidence is still insufficient to establish firm conclusions about cost-effectiveness and the most efficient means of delivery. Additional well-designed economic evaluations are needed. Other research aims include delineating the neurobiological underpinnings of ACT, refining available outcome and process measures or develop new ones for ACT trials, and meeting the challenge of wide dissemination and implementation in real-world clinical practice. Keywords: acceptance and commitment therapy, chronic pain, review, assessment, clinical evidence, cost-effectiveness